Structural design and performance study of permanent magnet safety coupling based on magnetorheological transmission technology - Zhang, Huirong; Song, Qinghua; Yao, Zhongfu; Wang, Jianxiang; Cai, Zeyang (Frontiers in Materials, 2024)
Based on magnetorheological transmission technology, a design for a permanent magnet safety coupling is proposed. Firstly, the structure scheme of the coupling is designed in detail, and its working principle and process are explained; Additionally, the influence of coupling structural parameters on magnetic field strength is studied by ANSYS, and the coupling's structural parameters are optimized; Finally, the prototype of the permanent magnet magnetorheological fluid coupling is tested for no-load characteristics and torque regulation characteristics through the preparation of magnetorheological fluid (MRF) and the construction of an experimental platform, the experimental results demonstrated that the prototype effectively transmits torque, and the no-load torque increases as the speed increases, at a motor speed of 400r/min, the experimental prototype achieves a maximum no-load torque of 2.6N.m; Under specific conditions of magnetic field strength and volume ratio, the torque transmitted by the coupling increases with the volume, for instance, when the volume of MRF is 50ml and a motor speed of 600r/min, the experimental prototype achieves a maximum torque value of 8.7N.m, additionally, when the volume is constant, the torque transmitted by the experimental prototype remains basically unchanged with the change of slip speed, showing the characteristic of constant torque,this study offers theoretical and practical insights for the design and experimental analysis of similar products.